The Effects of Cosmos caudatus (Ulam Raja) on Detoxifying Enzymes in Extrahepatic Organs in Mice - Azman Abdullah, Kezreen Kaur Dhaliwal, Nur Nabillah Fahana Roslan, Chai Hui Lee, Murali Kalaiselvam, Harizz Miszard Radman, Qodriyah Haji Mohd Saad, Kamisah Yusof, Kamsiah Jaarin (Journal of Applied Pharmaceutical Science, 2015)
‘Ulam Raja’ or Cosmos caudatus is a common appetizer (ulam) consumed by the Malay community in Malaysia. However, in vivo studies pertaining to its antioxidant and chemoprotective properties are lacking. This study was done to determine the effects of Cosmos caudatus on detoxifying enzymes in extrahepatic organs (lungs, kidneys and stomach) in mice. Thirty adult male white mice were treated orally for 21 days with different doses of ‘Ulam Raja’ aqueous extract (UR) (100, 500, 1000mg/kg). The control group was given normal saline by oral gavage. Mice fed with diet containing 0.5% butylated hydroxyanisole (BHA) were used as positive control. After 21 days, the mice were sacrificed and extrahepatic organs were harvested. The activities of several detoxifying enzymes [catalase (CAT), superoxide dismutase (SOD), glutathione S-transferase (GST), DT-diaphorase (DTD)] were measured. Lipid peroxidation level was determined by measuring malondialdehyde (MDA) concentration. In lungs, 100, 500 & 1000 mg/kg UR oral supplementation resulted in significant increases in CAT, SOD and GST activities. DTD activity in lungs was significantly increased in mice treated with 1000mg/kg UR. MDA levels in lungs were significantly decreased in mice treated with 100mg/kg & 500 mg/kg UR but was significantly increased in mice treated with 1000mg/kg UR. In kidneys, DTD activity was significantly increased in mice treated with 1000mg/kg UR. In stomach, CAT activity was significantly increased in mice treated with 1000mg/kg UR. The results showed that Cosmos caudatus supplementation in mice could protect extrahepatic organs from xenobiotic and oxidative injury. This indicates that consumption of ‘Ulam Raja’ might be a useful chemoprotective measure.
Keywords: Cosmos caudatus, mice, extrahepatic organs, detoxifying enzymes, antioxidant.